Left ventricular ejection fraction predicts outcomes in different subgroups of patients undergoing coronary angiography - Steffen, Henning Johann; Schupp, Tobias; Abumayyaleh, Mohammad S. A.; Kuhn, Lasse; Steinke, Philipp; Dudda, Jonas; Weidner, Kathrin; Rusnak, Jonas; Jannesari, Mahboubeh; Siegel, Fabian; Dürschmied, Daniel; Behnes, Michael; et al. (Journal of Clinical Medicine, 2025)
Objectives: To evaluate the long-term prognostic value of left ventricular ejection fraction (LVEF) in consecutive patients undergoing invasive coronary angiography (CA). Background: LVEF is a key prognostic marker in cardiovascular disease, but its value across different clinical indications for CA remains insufficiently characterized. Methods: Consecutive patients undergoing CA between January 2016 and August 2022 were retrospectively included at one institution. Patients were stratified into four LVEF groups: ≥ 55%, 45-54%, 35-44%, and <35%. The primary endpoint was rehospitalization for heart failure (HF) at 36 months. Secondary endpoints were acute myocardial infarction (AMI) and coronary revascularization. Kaplan-Meier and multivariable Cox regression analyses were conducted within the entire study cohort and pre-defined subgroups. Results: A total of 6888 patients were included (median age: 71 years; 65.2% males). LVEF < 35% was associated with a higher comorbidity burden and more extensive coronary artery disease (e.g., three-vessel CAD: 38.6% vs. 20.7%, p < 0.001). Event rates for HF rehospitalization and AMI increased progressively with declining LVEF, while revascularization rates varied across categories. Statistically significant differences across LVEF groups were observed for all three endpoints in unadjusted analyses (log-rank p < 0.001). In multivariable models, LVEF < 35% independently predicted HF rehospitalization (HR = 3.731, p < 0.001) and AMI (HR = 4.184, p < 0.001), but not revascularization (HR = 0.867, p = 0.378). The prognostic association was demonstrated across all subgroups stratified by age, sex, subtype of acute coronary syndrome, and CAD severity. Conclusions: Reduced LVEF is an independent predictor of HF rehospitalization and AMI in patients undergoing coronary angiography, irrespective of its indication, whereas no independent association was observed with coronary revascularization.